2021
DOI: 10.3390/rs13163150
|View full text |Cite
|
Sign up to set email alerts
|

Building Change Detection Method to Support Register of Identified Changes on Buildings

Abstract: Based on a newly adopted “Rulebook on the records of identified changes on buildings in Serbia” (2020) that regulates the content, establishment, maintenance and use of records on identified changes on buildings, it is expected that the geodetic-cadastral information system will be extended with these records. The records contain data on determined changes of buildings in relation to the reference epoch of aerial or satellite imagery, namely data on buildings: (1) that are not registered in the real estate cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Chang et al [25] have shown that using OBIA techniques can substantially overcome issues associated with the per-pixel method, and these are capable of more precisely defining a spatially complex urban area by successfully distinguishing between settlement types [20,24,26]. Several researchers, including Ghaffarian and Emtehani [27], Kohli et al [28] and Jovanović et al [29], have studied the use and effectiveness of OBIA. They concluded that OBIA produces highly accurate results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chang et al [25] have shown that using OBIA techniques can substantially overcome issues associated with the per-pixel method, and these are capable of more precisely defining a spatially complex urban area by successfully distinguishing between settlement types [20,24,26]. Several researchers, including Ghaffarian and Emtehani [27], Kohli et al [28] and Jovanović et al [29], have studied the use and effectiveness of OBIA. They concluded that OBIA produces highly accurate results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Object-based machine learning algorithms are becoming an area of interest in feature extraction [41][42][43]. The RF classification algorithm is an ensemble of decision trees trained using a combination of learning models [44].…”
Section: Random Forest Classifiermentioning
confidence: 99%
“…This is the knowledge gap that the authors wanted to address. Some of the important objects, the disclosure of which in the cadastre database causes significant consequences for both their owner and the municipality, are buildings [27,28].…”
Section: Introductionmentioning
confidence: 99%